Development of a Cerium bromide gamma ray spectrometer for space applications. Issue 6 (15th September 2017) - Panda, D.K.; Banerjee, D.; Goyal, S.K.; Patel, A.R.; Shukla, A.D.
Abstract: We present the development of a CeBr3 gamma ray spectrometer with the primary objective of determining the abundance and distribution of Th, U, K, Fe, Al and Si by measuring gamma ray signals produced by radioactive decay, neutron inelastic scattering and neutron capture reactions in the energy region 0.03–8 MeV. The energy resolution of the CeBr3 gamma ray spectrometer developed in-house has been measured at 662 and 1274 keV to be 4.0% and 2.8% respectively. The intrinsic activity count-rate for the 1″ × 1″ CeBr3 gamma ray spectrometer is ∼0.03 counts s −1 for the 40 K energy window (1400–1520 keV), and ∼0.001 counts s −1 for the 232 Th (2550–2700 keV) energy window. The U concentration of a sample (3A) from a granite rock was estimated to be ∼2.1 ppm and agrees with the 2.04 ppm value determined using a HPGe gamma ray spectrometer. The K concentration of sample 3A was estimated to be 3.8%, and is consistent with the 3.7% value determined independently using a HPGe gamma ray spectrometer.